RNAi: rISC gets loaded. - Preall, J.B.; Sontheimer, E.J. (Cell, 2005)
When an siRNA or miRNA proceeds through the RNA-induced silencing complex assembly pathway, only one of the two approximately 21-nucleotide RNA strands survives in the final, active complex. In this issue of Cell, Matranga et al. (2005) and Rand et al. (2005) reveal the fate of the rejected passenger siRNA strand. Additionally, Gregory et al. (2005) define a heterotrimeric complex from humans that appears to execute dsRNA loading, strand selection, and target mRNA cleavage activities.